Human Resource Capacity and Integrated Information Systems for Financial Governance Optimization - Musyafak Musyafak; Yundy Hafizrianda; Hasan Basri Umar (Goodwood Publishing, 2026)
Purpose: This study formulates integrated strategies for strengthening human resource capacity and implementing an integrated regional information system to optimize financial administrative governance at the Secretariat of the Regional House of Representatives (Dewan Perwakilan Rakyat Daerah [DPRD]) of Mimika Regency, Papua Tengah Province, Indonesia.Methodology: A mixed-methods strategic planning design was employed. Primary data were collected through a structured questionnaire administered to all 17 personnel involved in financial administration and information-system operations, using a modified Likert scale ranging from zero to four. Analysis combined weighted scoring of three research variables, Internal Factor Analysis Summary and External Factor Analysis Summary matrices, SWOT strategy formulation, and Quantitative Strategic Planning Matrix prioritization, following the strategic management framework of David (2016) and Rangkuti (2014).Results: Human resource capacity obtained the highest variable weight of 0.38, followed by financial governance at 0.37 and information-system implementation at 0.25. The internal and external factor scores of 3.44 and 3.45 positioned the organization in the aggressive-growth quadrant, and structured technical and managerial training emerged as the top-ranked strategy with a Total Attractiveness Score of 5.98.Conclusions: Optimizing financial administrative governance requires synergistic integration of human resource strengthening and information-system optimization, with human resource development as the primary strategic driver.Limitations: The single-unit design with 17 respondents restricts statistical generalization.Contributions: The study offers an integrated strategic planning model transferable to comparable resource-rich regional legislative secretariats.